Experimental investigation of the fire resistance of partially encased beams - Piloto, P.A.G. (2013)
This research presents the fire resistance of Partially Encased Beams (PEB). Fire resistance was determined by means of twelve experimental tests, according to European standard EN1363-1, for different load levels and shear conditions between stirrups and web steel. Three tests were also performed at room temperature for load bearing resistance. The experimental setup was designed for this purpose, using a small fire resistance furnace and portal reaction frame. Details about the specimens tested, the instruments used and the characteristics of the materials, are also presented. Load-deflection and load-strain results were determined at room temperature. Deflection and temperature measurements were determined under ISO834 fire exposure. Results reveal the dependence of fire resistance on load level. An increase in 37% on load level is responsible for a decrease in 28% on fire resistance. Tests developed for the highest load level present similar fire resistance, independently of the shear condition; however, tests with welded stirrups present higher critical time. The main experimental results are presented and discussed. Particular emphasis was given to changes in temperature for each material, and on the global thermo-mechanical behaviour of this composite steel and concrete element.